Brain functional magnetic resonance imaging in ICU patients who developed delirium - Song, Ren-Jie; Guo, Fu-Jian; Huang, Xiao-Fei; Li, Mo; Sun, Yi-Yun; Yu, An-Yong; Zhang, Tian-Xi (Frontiers in Physics, 2024)
Objective: To detect brain alterations in intensive care unit (ICU) patients with delirium using functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) and to determine their predictive value. Methods: Fifty-two patients who were admitted to the ICU of the Affiliated Hospital of Zunyi Medical University between June 2021 and June 2022 were enrolled. Fifteen patients who were diagnosed with delirium by the Intensive Care Delirium Screening Checklist (ICDSC) after MRI were selected as the delirium group, and fifteen healthy volunteers during the same period served as the control group. Both groups underwent fMRI and DTI. Quantitative fMRI and DTI data were compared to detect abnormal structural and functional brain damage. The relationships between MRI outliers and clinical indicators in the delirium group were also assessed. Results: Demographic characteristics and imaging indicators before delirium were not correlated with ICDSC scores after delirium. Compared with the healthy control group, the delirium group had significantly lower regional homogeneity (ReHo) values in the left caudate nucleus and frontal lobe on fMRI. The amplitude of low-frequence fluctuations (ALFF) values of the delirium group were significantly increased in the hippocampus but significantly decreased in the frontal lobe. Compared with the healthy control group, the delirium group showed reduced MD values, mainly in the right cerebellum and right middle temporal gyrus; reduced RD values, mainly in the anterior cerebellum and right middle temporal gyrus; reduced FA values, only in the corpus callosum; and reduced AD values, mainly in the anterior cerebellar lobe, right middle temporal gyrus and left middle frontal gyrus on DTI. The statistical thresholds for quantitative DTI measurements were P<0.005 at the voxel level and a cluster size>5. Conclusions: Abnormal resting-state brain activity in the left superior frontal gyrus and structural changes in the frontal lobe, temporal lobe, corpus callosum, hippocampus and cerebellum were observed in ICU patients with delirium during hospitalization. Early brain fMRI and DTI examinations are recommended for the prediction of delirium according to unique quantitative indicators to facilitate early intervention for critically ill patients, reduce the length of hospital stay and improve patient prognosis.